Multicentric Leptomeningeal Glioblastoma Mimicking Meningioma: A Case Report and Systematic Review - Mishra, Rakesh; Bhat, Dhananjaya I.; Gupta, Ankit A.; Devi, Indira B.; Rao, Shilpa (Indian Journal of Neurosurgery, 2025)
Extra-axial glioblastoma is rare. We report the first case of multicentric extra-axial sellar glioblastoma mimicking a meningioma and systematic review on its pathogenesis following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. The case report follows the CAse REport guidelines. With this review a series of cases, including our case, is presented.Case presentation: A 73-year-old gentleman had an extra-axial lesion in the sellar region and a left clinoid mimicking a meningioma. Dense dural and vessel adhesions restricted resection to subtotal decompression. Histopathology was isocitrate dehydrogenase (IDH) wild-type glioblastoma.We searched databases as per the PRISMA guidelines for articles on extra-axial glioblastoma, leptomeningeal glioblastoma, and cases where glioblastoma mimic meningioma. We analyzed demographics, clinical presentation, surgical challenges, histopathology, and immunohistochemistry.We identified 793 articles, of which 9 articles, 12 patients (including our case), matched our inclusion criteria. Most of the patients were elderly with a mean age of 56.9 years (range; 33–74 years); male:female of 8:4. The majority had headaches without raised intracranial pressure. The most common mimicking pathology was meningioma. Adhesions to brain, major vessels, and pial invasion made complete excision impossible in most patients. IDH wild-type tumors had middle meningeal artery blush in angiogram.Extra-axial/primary-intracranial-leptomeningeal-glioblastoma is a tumor subtype with specific clinical/radiological features, extent of resection, and outcomes. As glioblastoma prognosis differs significantly from meningioma, extra-axial glioblastoma's identification is essential for decision-making and prognostication. There is an early trend suggesting that primary leptomeningeal glioma prognosis may not be worse than classic glioblastoma. This case adds to knowledge on pathogenic mechanisms and variable representation of glioblastoma.
Keywords: glioblastoma; primary intracranial leptomeningeal glioblastoma; sellar glioblastoma; meningioma; multicentric glioblastoma; case report